Advancing Children’s Right to Migration in Canada: Assessing the Participatory Rights of Unaccompanied Children in their Refugee Claim Process - Ciufo, Dustin (Refuge, 2024)
This paper applies Laura Lundy’s model for children’s participation to conduct a critical examination into the participatory rights of unaccompanied children as they encounter the Canadian Border Services Agency (CBSA) and the Immigration and Refugee Board (IRB) of Canada. The findings of this study reveal that while more child-adaptable measures are implemented by the IRB in contrast to the CBSA, each institution requires addressing significant gaps in children’s rights to specifically uphold the participatory rights of unaccompanied children throughout their refugee claim process in Canada.